Poradní kruh jako součást školní praxe - Banďouchová, Petra (Masaryk University Press, 2022)
Title in English: Council as a part of the school practice The present text serves as a methodological guide for teachers to be and students of other pedagogical disciplines, pedagogical staff of schools and educational institutions for introducing the practice of council in groups of children and youth. The text introduces the importance of sharing stories with each other as a starting point for further academic and social learning. The handbook then briefly describes the characteristics of working in council, providing concrete suggestions and examples from practice. Finally, the experience with advisory circles is presented through the eyes of a practising teacher and students of the Faculty of Education at Masaryk University.